Comparative Antibacterial and Antifungal Studies with Different Plant Extracts - Mukherjee, Jayanti; Varshitha, Peddi; Shruthi, Pothulapalli; Sanjana, Nagulapally; Rao, T. Rama (Asian Journal of Pharmaceutical Research and Development, 2024)
In the present scenario, resistance of pathogenic microorganisms to the most of antimicrobial (antibacterial and antifungal) agents is increasing. In this study we have compared the antibacterial and antifungal effect of some medicinal plants like neem, turmeric and ginger. The methanol extracts of these plants were prepared for determining their anti-bacterial and anti-fungal activity. Then comparative analysis of antibacterial effects between those extracts were tested in E. Coli and Bacillus subtilis culture. Also, the antifungal activity of these extractswas tested and compared using Saccharomyces cerevisiae culture. The antibacterial and antifungal activity was investigated using well diffusion method. All of the extracts have shown antibacterial and antifungal activity. The methanolic herbal extracts of ginger, turmeric rhizomes and neem leaves exhibit promising antibacterial properties against E. Coli and Bacillus subtilis and antifungal properties against Saccharomyces cerevisiae.